A study of the possibility of evasion minimization in distance education supported by alternative therapy (Research, Society and Development, 2019)
Distance Education (EaD) is an educational modality in which there is a high level of avoidance. Several factors can cause evasion and one of them is depression. The decrease of this factor can contribute to the minimization of evasion in this modality. We believe that low-cost and non-drug alternative therapies may be useful in this type of difficulty. This article aims to present a study that seeks to unveil the possibility of non - drug alternative therapy. We carried a study in which one makes use of therapy through social media. The study is a social research that occurred in the first half of 2017, with 5 participants, who in principle had problems that would lead them to give up their EaD courses. We treated research participants in the first half of 2017. Four did not give up the course. The results indicated that alternative therapy shown to be effective in decreasing the use of antidepressants, improving the sense of well-being and therefore reducing avoidance.